Nitrous oxide–induced reproductive risks: Should recreational nitrous oxide users worry?. (August 2022) - van Amsterdam, Jan; van den Brink, Wim
Background: Nitrous oxide (N2 O) is a frequently used anaesthetic. Since the year 2000, recreational use of N2 O, also known as 'laughing gas', became popular as a recreational drug due to its mild psychedelic effect. In the 1980s, several reports warned against N2 O-induced reproductive risks among healthcare personnel, questioning the occupational safety of N2 O in health care. Methods: Data about the reproductive risks of N2 O were collected from literature. Results: Particularly in the past, professionals working in dental and midwifery practices, operating theatres and ambulance transport were exposed to high levels of N2 O. Adverse reproduction effects included congenital anomalies, spontaneous abortion and reduced fertility rates in females. Following occupational measures, like maximal exposure limits for ambient N2 O, this occupational risk was considerably reduced. Recreational users of N2 O, however, voluntarily and repeatedly expose themselves to (very) high doses of N2 O. As such, they exceed the health exposure limits some hundred times, but they are fully unaware of the related reproductive risks. Conclusion: We advocate to increase the awareness in recreational N2O-users about its potential reproductive risks, especially in heavy users, pregnant users or those who intend to become pregnant.